Neoarchaean crustal evolution along the eastern flank of Nallamalai Shear Zone, southern India. Issue 21 (30th November 2022) - Thanooja, P. V.; Santosh, M.; Li, Shan-Shan; Nandakumar, V.; Ishwar-Kumar, C.
ABSTRACT: The Southern Granulite Terrane (SGT) in India is composed of Archaean to Proterozoic crustal blocks and intervening shear/suture zones. The Nallamalai shear zone lies along the eastern flank of the Shevaroy Block. This study is focused on the eastern part of this shear zone where the basement rocks are dominantly composed of charnockite, quartzo-feldspathic gneiss and metagabbro, all of which preserve original magmatic texture. Zircon U-Pb LA-ICPMS analysis on the charnockite samples yielded an age of 2680 to 2500 Ma for the protolith emplacement followed by metamorphism at 2520 to 2450 Ma. Magmatic zircon grains in the quartzo-feldspathic gneiss and metagabbro yielded weighted mean ages of ca . 2557 Ma and ca . 2583 Ma with metamorphism at ca . 2518 Ma. Zircon Lu-Hf data suggest that the protolith of metagabbro was sourced mainly from the recycled Mesoarchaean crustal component. The ƐHf (t) of charnockite (−0.4 to 4.1) and quartzo-feldspathic gneiss (0.5 to 6.0) represent a combined source of the mantle as well as recycling crust. All the rocks underwent amphibolite to granulite facies metamorphism and petrological studies and pseudosection modelling shows a similar P-T range of 7 – 8 kbar and 650 – 830°C. Results from the present study suggest that crustal evolution along the eastern flank of the Nallamalai Shear Zone involved melting of older crustal components (Mesoarchaean age) with significant juvenile input (ƐHf (t)  = ~+6.0) within a continental arc setting.